The ethics of dark comedy - Lee, Hanna (Nanyang Technological University, 2024)
Dark comedy refers to a specific category of comedy that deals with subjects that are perceived to be taboo, sensitive or morbid in nature. Within the realm of dark comedy, it is often difficult to establish when a joke can go “too far”. Underlying this difficulty appears to be the notion held by enjoyers of dark comedy that humour is not meant to be taken seriously. As such, there is no real basis for harm to result. In this paper, I argue that real harm can result from instances of dark comedy, making such instances impermissible. I do so by attempting to establish a singular minimum boundary that demarcates impermissible dark humour from permissible dark humour in the context of comedy.